Impact of Organizational Culture on Perceptions of Career Success among Women - Kluska-Nowicka, Małgorzata (Wpływ kultury organizacyjnej na postrzeganie sukcesu zawodowego wśród kobiet, 2025)
Aim: The objective of this study is to determine the impact of organizational culture on women’s career success and their perception of success, taking into account the interrelationships between variables. Methodology: The research encompasses a literature review and quantitative analysis using the CAVI method. The sample set consisted of 45 respondents. The article is based on empirical research conducted in 2024. Relationships between variables were analyzed using Spearman correlation and regression. Results: The results partially confirmed the hypothesis that organizational culture influences women’s perception of career success. Specifically, organizational culture exhibiting feminine characteristics and the elimination of gender stereotypes promote women’s sense of career success. Implications and recommendations: Inclusiveness, work-life balance, mentoring, and flexible forms of employment were key factors identified as supporting women’s career development. Furthermore, a key contributor in this transformation is the transition from traditional masculine organizational structures towards more feminine models. Given the rapid pace of social and economic changes, consistent and systematic examination of organizational culture appears to be justified. Originality/value: The results presented in this research highlight the factors that may contribute to promoting women’s career development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 64-79